Creep of mullite zirconia composites. Issue 13 (November 2015) - Glymond, D.; Vick, M.; Pan, M.-J.; Giuliani, F.; Vandeperre, L.J.
Abstract: The compressive creep resistance of two zirconia mullite composites and a monolithic mullite was measured. The zirconia additions were either monoclinic zirconia or 5.4 mol% yttria stabilised zirconia. Samples were tested between 1225 °C and 1500 °C. It was found that the addition of zirconia lowered the creep resistance of monolithic mullite (5.8 × 10 −7  s −1 at 1400 °C, 13 MPa), with yttria stabilised zirconia (3.3 × 10 −5  s −1 ) having a greater effect than monoclinic zirconia (3.4 × 10 −6  s −1 ) under equal conditions. The lower creep resistance of the composites is consistent with creep being controlled by oxygen diffusion as the changes in creep rate can be explained using the effective oxygen diffusion coefficients for the composites calculated from literature values for oxygen diffusion in mullite and zirconia.